2006
DOI: 10.1001/archinte.166.9.997
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes Using 2 Delivery Models of Anticoagulation Care

Abstract: Background: Studies demonstrate the effectiveness of anticoagulation management service (AMS) in providing antithrombotic therapy for eligible patients. We sought to extend this concept by determining whether an interim telephone model (IT) is comparable to our current AMS model at achieving optimal therapeutic outcomes. Methods:The 36-month trial (24-month study plus 12month extension) enrolled 192 eligible patients receiving long-term warfarin therapy at a Veterans Affairs hospital. Consenting participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 18 publications
2
38
2
1
Order By: Relevance
“…Of these, 16 studies were excluded because patients were included for indications other than AF. 14,15,19,[22][23][24][25][27][28][29][30][32][33][34]36,37 Thus, 8 studies, including a total of 14 study groups, met all of the inclusion criteria and were included in the final analysis (Table 1). 17,18,20,21,26,31,35,38 The study groups enrolled a median of 317 patients (interquartile range, 150 to 482 patients; total = 22,237 warfarintreated patients), 31 who were followed for a median of 272.3 patient-years (range, 123.9 to 980.8 patient-years; total = 41,471.9 patient-years).…”
Section: ■■ Resultsmentioning
confidence: 99%
“…Of these, 16 studies were excluded because patients were included for indications other than AF. 14,15,19,[22][23][24][25][27][28][29][30][32][33][34]36,37 Thus, 8 studies, including a total of 14 study groups, met all of the inclusion criteria and were included in the final analysis (Table 1). 17,18,20,21,26,31,35,38 The study groups enrolled a median of 317 patients (interquartile range, 150 to 482 patients; total = 22,237 warfarintreated patients), 31 who were followed for a median of 272.3 patient-years (range, 123.9 to 980.8 patient-years; total = 41,471.9 patient-years).…”
Section: ■■ Resultsmentioning
confidence: 99%
“…They show that researchers must continue to evaluate interventions, including anticoagulation clinics, 47,58,59 patient self-management [60][61][62] and telephone communication systems, 63 that increase the amount of time at which patients' international normalized ratios are within the therapeutic range.…”
Section: Discussionmentioning
confidence: 99%
“…The PCMH model generally makes use of interdisciplinary teams to communicate with patients in a comprehensive, coordinated and efficient way [1]. Though primary care clinics have long communicated with patients through telephone, usually as a response to patient initiated requests or to follow-up on a specific procedure [2], the telephone and other forms of remote communication are now promoted as alternatives to traditional face-to-face visits, offering patients more flexibility with encounter modes and schedules [3]. Accordingly, more policies are covering telephone-based care, although reimbursement varies by state and may depend on approach, such as integrating video with audio conferencing [4-6].…”
Section: Introductionmentioning
confidence: 99%
“…Although prior studies have shown that telephone visits can successfully replace in-person care for focused issues, such as follow-up or monitoring [3,10,11], there is little information on how it works for more complex and multifaceted tasks of care coordination, chronic disease management, and preventive health care typically provided in a primary care visit. One study on the impact of substituting telephone care for some VHA clinic visits showed that this mode, with more frequent contact but fewer face-to-face interactions, lowered rates of healthcare utilization with no adverse effects on patient satisfaction [12].…”
Section: Introductionmentioning
confidence: 99%